Changes in care : aging, migration, and social class in West Africa - Coe, Cati (Global perspectives on aging series., 2021)
"Africa is known both for having a primarily youthful population and for its elders being held in high esteem. However, this situation is changing: people in Africa are living longer, some for many years with chronic, disabling illnesses. In Ghana, many older people, rather than experiencing a sense of security that they will be respected and cared for by the younger generations, feel anxious that they will be abandoned and neglected by their kin. In response to their concerns about care, they and their kin are exploring new kinds of support for aging adults, from paid caregivers to social groups and senior day centers. These innovations in care are happening in fits and starts, in episodic and scattered ways, visible in certain circles more than others. By examining emergent discourses and practices of aging in Ghana, Changes in Care makes an innovative argument about the uneven and fragile processes by which some social change occurs. There is a short film that accompanies the book, "Making Happiness: Older People Organize Themselves" (2020), an 11-minute film by Cati Coe. Available at: https://doi.org/doi:10.7282/t3-thke-hp15"--